Cost-effectiveness of total shoulder arthroplasty compared with hemiarthroplasty: a study using data from the National Joint Registry - Andrew Davies; Amar Rangan; Martinique Vella-Baldacchino; Alexander D Liddle; Sanjeeve Sabharwal; Peter Reilly; Bernarda Zamora-Talaya (BMJ Open)
Objectives The aim of this study was to compare the cost-effectiveness of total shoulder arthroplasty (TSA) and hemiarthroplasty (HA) and explore variation by age and gender.Design Cost-effectiveness analysis using a lifetime cohort Markov model.Setting National population registry data.Participants Model parameters were informed by propensity score-matched comparisons of TSA and HA in patients with osteoarthritis and an intact rotator cuff using data from the National Joint Registry.Interventions TSA and HA.Primary outcome measures Quality-adjusted life years (QALYs) and healthcare costs for age and gender subgroups. A probabilistic sensitivity analysis was performed.Results In all subgroups, TSA was more cost-effective, with the probability of being cost-effective about 70% for TSA versus 30% for HA at any willingness-to-pay threshold above £1100 per QALY. TSA was dominant in young patients (≤60 years) with a mean cost saving of £463 in men and £658 in women, and a mean QALY gain of 2 in both men and women. In patients aged 61–75 years, there was a mean cost saving following HA of £395 in men and £181 in women, while QALYs remained superior following TSA with a 1.3 gain in men and 1.4 in women. In the older cohort (> 75 years), the cost difference was highest and the QALY difference was lowest; there was a cost-saving following HA of £905 in men and £966 in women. The mean QALY gain remained larger after TSA: 0.7 in men and 0.9 in women.Conclusion TSA was more cost-effective than HA in patients with osteoarthritis. QALYs were superior following TSA in all patient groups. Cost differences varied by age and TSA was dominant in young patients.